Sculptuur Park Sebrechts : Aspecten '86. - Park Sebrechts, Brugge (Brugge : Stadsbestuur Brugge, 1986)
Martens, Michel ; Verlinde, Blanche ; Rubens, Albert ; Scafoglieri, Angelo ; De Blok, Luc ; Verbeke, Jan Karel ; Watty, Werner ; De Clercq, R. Amea ; Jonckheere, Anne-Marie ; Bossuyt, Werner
Sculptuur Park Sebrechts : Aspecten '86, Stadsbestuur Brugge, 5 juli tot 6 september 1986
boek